DutaFabs are engineered therapeutic Fab fragments that can bind two targets simultaneously - Roland Beckmann (Nature Portfolio, 2021)
Bispecific antibodies can bind to two distinct targets though the fusion of two different Fv regions. In this study, the authors develop DutaFabs that present two separated and independent antigen binding sites within the same Fv region, giving rise to bispecific Fab fragments.